Distensibility and Pain of the Uterine Cervix Evaluated by Novel Techniques. Issue 2 (June 2017) - Gregersen, H.; Hee, L.; Liao, D.; Uldbjerg, N.
Abstract : ( Acta Obstet Gynecol Scand . 2016;95(7):717–723) Functional luminal imaging probe (FLIP) is a new distension technology that is used to study cervical distension. Initially, this technology was designed in order to examine the biomechanical competence of the gastro-esophageal junction as it helps to generate a geometric profile of the lumen during distension. The purpose of this article was to assess the literature since 2002 on the use of FLIP for studying cervical distension.